Multilocus genetic diversity and historical biogeography of the endemic wall lizard from Ibiza and Formentera, Podarcis pityusensis (Squamata: Lacertidae). Issue 19 (21st August 2013) - Rodríguez, V.; Brown, R. P.; Terrasa, B.; Pérez‐Mellado, V.; Castro, J. A.; Picornell, A.; Ramon, M. M.
Abstract: Two monophyletic sister species of wall lizards inhabit the two main groups of Balearic Islands: Podarcis lilfordi from islets and small islands around Mallorca and Menorca and Podarcis pityusensis from Ibiza, Formentera and associated islets. Genetic diversity within the endangered P. lilfordi has been well characterized, but P. pityusensis has not been studied in depth. Here, 2430 bp of mtDNA and 15 microsatellite loci were analysed from P . pityusensis populations from across its natural range. Two main genetic groupings were identified, although geographical structuring differed slightly between the mtDNA and the nuclear loci. In general, individuals from islets/islands adjacent to the main island of Ibiza were genetically distinct from those from Formentera and the associated Freus islands for both mtDNA and the nuclear loci. However, most individuals from the island of Ibiza were grouped with neighbouring islets/islands for nuclear loci, but with Formentera and Freus islands for the mitochondrial locus. A time‐calibrated Bayesian tree was constructed for the principal mitochondrial lineages within the Balearics, using the multispecies coalescent model, and provided statistical support for divergence of the two main P . pityusensis lineages 0.111–0.295 Ma. This suggests a mid‐late Pleistocene intraspecific divergence, compared with an early Pleistocene divergence in P. lilfordi, and postdates some major increases in sea level between 0.4 and 0.6 Ma, which may have flooded Formentera. The program IMa2 provided a posterior divergence time of 0.089–0.221 Ma, which was similar to the multispecies coalescent tree estimate. More significantly, it indicated low but asymmetric effective gene copy migration rates, with higher migration from Formentera to Ibiza populations. Our findings suggest that much of the present‐day diversity may have originated from a late Pleistocene colonization of one island group from the other, followed by allopatric divergence of these populations. Subsequent gene flow between these insular groups seems likely to be explained by recent human introductions. Two evolutionary significant units can be defined for P. pityusensis but these units would need to exclude the populations that have been the subjects of recent admixture.